THE IMPORTANCE OF MODIFICATIONS OF VOWELS IN CONNECTED SPEECH - Teshaboyeva Nafisa Zubaydulla qizi; Marina I. Solnyshkina; Mirzaaliyeva Maftuna ("Conference on Universal Science Research 2023", 2023)
This comprehensive article delves into the intricate world of vowel modifications in connected speech, shedding light on the nuanced changes that occur in spoken language. The author adeptly navigates through various phenomena, such as assimilation, vowel reduction, elision, and linking, providing clear examples and explanations for each. Notably, the article emphasizes the dynamic natureof these modifications, highlighting their dependence on context, speech patterns, and regional accents. The incorporation of practical examples, such as phrases and words, aids in illustrating the concepts, making them accessible to both language learners and linguistics enthusiasts. Moreover, the article underscores the significance of understanding vowel modifications in enhancing both comprehension and production of spoken language. Overall, this article serves as an insightful guide, offering valuable insights into the complexities of vowel modifications in connected speech